EDUCATIONAL INEQUALITES IN THE VIEW OF POLISH SOCIOLOGY OF EDUCATION - Długosz, Piotr (Youth in Central and Eastern Europe. Sociological Studies, 2015)
The paper presents the output of Polish sociology of education. The author shows research projects and thematic fields present in the work of Polish scientists. The conducted research focuses on old educational inequalities (the impact of status on educational achievements and aspirations) as well as the new ones (the impact of status on private lessons and additional classes). In the article the consequences of socioeconomic transformation and their impact on educational inequalities is shown as well. At the end, the theoretical concepts of cultural capital, human capital and credentialism, helpful with the analysis and explanation of social inequalities in Poland are shown as well
Keywords: educational inequalities; Poland; transformation; private tutoring; human capital; cultural capital